Konstruksi Ideal Pengaturan Hak Ingkar Notaris Pasca Berlakunya Putusan Mahkamah Konstitusi Nomor 49/Puu-X/2012 dan Perubahan Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris - Ardana Restika (Universitas Islam Indonesia, 2016)
AbstractThe study examines the issue of how the ideal construction legal protection of the right of refusal and whether the right of refusal Notary Notaries can be used to reject as a witness in court. The method used is a normative juridical research comes with empirical data, the approach is based on the development of legislation in force and the facts on the ground. Then performed a qualitative analysis afterwards classify, identify and evaluate the data obtained in order to determine and find answers to the problems that dibahas. These studies show that UUJNP has met the legal basis and sociology, but do not meet the filososfis runway. Legislation can be said to fulfill the ideal construction when it justice, law and order. Notary right of refusal can be used to reject as a witness in court, as in Article 1870 of the Civil Code that the Notary deed as authentic deed has the strength of evidence was perfect and the Notary as positions of trust in their duties shall keep secrets about deed made by or in front of Notary.Keywords: Ideal Construction, Notaries Right of Refusal.